The COVID-19 Pandemic and Everyday Life: The Relations of Lockdown, Social Distancing, Face Masking, Discreet Salutation and Hand Hygiene in Nigeria - Omobowale, Ayokunle Olumuyiwa; Falase, Olugbenga Samuel; Oyelade, Olufikayo Kunle; Omobowale, Mofeyisara Oluwatoyin (Sociološki pregled, 2020)
This paper provides a contextual discourse on the COVID-19 pandemic and the consequent reality of taken-for-granted nuances using the epistemology of everyday sociology. The COVID-19 pandemic has become a global disease that has virtually affected all facets of life. Nigerian government has moved swiftly to curb the pandemic through containment protocols of lockdown, social distancing, face masking, discreet salutation and hand hygiene. As social actors continue to interact amid the pandemic, they construct and reconstruct the world around them through the social interpretations and contextual meanings derived from these containment protocols. The taken-for-granted nuances and meanings embedded in these micro interpretations allow social actors to take interpretive actions based on the meanings attached to COVID-19 pandemic and the containment protocols.